THE GEOLOGY OF THE ZLATIBOR-MALJEN AREA (WESTERN SERBIA): A GEOTRAVERSE ACROSS THE OPHIOLITES OF THE DINARIC-HELLENIC COLLISIONAL BELT - Chiari, Marco; Djerić, Nevenka; Garfagnoli, Francesca; Hrvatović, Hazim; Krstić, Marko; Levi, Nicola; Malasoma, Alessandro; Marroni, Michele; Menna, Francesco; Nirta, Giuseppe; Pandolfi, Luca; Principi, Gianfranco; et al. (Ofioliti, 2011)
In this paper, we describe the stratigraphic and structural features of the tectonic units cropping out along the Zlatibor-Maljen geotraverse, located in western Serbia at the boundary with Bosnia-Herzegovina, and we present also a 1:100,000 scale geological map. The study area corresponds to a SSW-NNE geotraverse, where the main oceanic and continental tectonic units of the Dinaric-Hellenic belt are well exposed. Along this geotraverse, the tectonic pile includes at the top the units derived from the European Plate, here represented only by the Ljig Unit, that was thrust over the oceanic units, cropping out in two distinct massifs, the Zlatibor and Maljen ones. In both massifs the oceanic units consist of a sub-ophiolite mélange overthrust by an ophiolite unit represented exclusively by mantle peridotites with the metamorphic sole at their base. In turn the oceanic units are overthrust the Adria-derived units, here represented by the East Bosnian-Durmitor and Drina-Ivanjica Units, respectively located westward and eastward of the Zlatibor Massif. The geological data and the tectonic reconstruction suggest that the ophiolites of the two s may have originated in the same composite oceanic basin that experienced oceanic opening, intra-oceanic subduction, development of supra-subduction oceanic basins and finally closure, in a time span ranging from Middle Triassic to Late Jurassic. The stratigraphic and structural dataset presented in this paper allows some insights about the geodynamic history of the northern area of the Dinaric-Hellenic belt, as well as a comparison with the reconstructions proposed for the southernmost area by other authors.